Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai pada Sub Bagian Tata Usaha Kantor Imigrasi Kelas I Non TPI Depok - Luthfia Alfianti; Taat Kuspriyono (JURNAL RISET MANAJEMEN (JURMA), 2024)
Increasing human resources in developing organizational management is the key to increasing competitiveness and independence in the era of globalization. In this context, the government is trying to prepare State Civil Apparatus (ASN) that are professional, have competitiveness, and can anticipate rapid global changes in various areas of life. This ASN is also expected to have quality service capabilities and be able to improve performance significantly. Every government agency is required to be able to optimize its human resources to achieve organizational goals.